Auditoría de gestión al componente talento humano de la empresa muñoz diseño topográfico y construcciones cía. ltda., período del 1 de octubre al 31 de diciembre de 2015, para determinar su desempeño. - Quinzo Zula, Fernando Patricio (2017)
This study was performed in the Company “Muñoz Diseño Topográfico y Construciones” Its main economic activity is the topographic studies, at national level; also there are other services such as: Exploration, exploitation and commercialization of mining of any type, demolition work; Landfilling and land cutting grass; beside excavation and earthmoving work, water well drilling services. Other services the company provides are the import, distribution, purchase, sale and leasing of heavy truck equipment; motor grader, rollers, backhoe loaders, crawler excavators, crawler tractors, mini loaders. With a rigorous management audit, the absence of process evaluation in terms of efficiency, and economy has been determined. Reason for which, it was necessary to evaluate the planning, direction and in internal control; In addition to verifying its efficiency, and economy, with which the human talent was employed, beside the results of its operations, in order to determine the fulfillment of the main goals and objectives.